2007
DOI: 10.1128/jvi.01911-06
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Attenuation of Vesicular Stomatitis Virus by Combination of Specific G Gene Truncations and N Gene Translocations

Abstract: A variety of rational approaches to attenuate growth and virulence of vesicular stomatitis virus (VSV) have been described previously. These include gene shuffling, truncation of the cytoplasmic tail of the G protein, and generation of noncytopathic M gene mutants. When separately introduced into recombinant VSV (rVSV), these mutations gave rise to viruses distinguished from their "wild-type" progenitor by diminished reproductive capacity in cell culture and/or reduced cytopathology and decreased pathogenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 63 publications
7
106
1
Order By: Relevance
“…To directly evaluate neurotoxicity, escalating doses of rVSV (GP), rVSV, or the attenuated matrix protein-mutated rVSVDM51 virus were injected into the brains of CD-1 and Balb/c mice. Consistent with previous reports (21,22), all cohorts treated with VSV-G-expressing strains (doses as low as 10 1 PFU) succumbed to neurologic symptoms including significant weight loss by 9 days postinfection (dpi) (Fig. 1A-C).…”
Section: Chimeric Lcmv:vsv Viruses Lack Neurotoxicitysupporting
confidence: 78%
See 1 more Smart Citation
“…To directly evaluate neurotoxicity, escalating doses of rVSV (GP), rVSV, or the attenuated matrix protein-mutated rVSVDM51 virus were injected into the brains of CD-1 and Balb/c mice. Consistent with previous reports (21,22), all cohorts treated with VSV-G-expressing strains (doses as low as 10 1 PFU) succumbed to neurologic symptoms including significant weight loss by 9 days postinfection (dpi) (Fig. 1A-C).…”
Section: Chimeric Lcmv:vsv Viruses Lack Neurotoxicitysupporting
confidence: 78%
“…We removed the VSV glycoprotein G, the key neurovirulence determinant (20)(21)(22), and replaced it with the arenavirus glycoprotein LCMV-GP (23)(24)(25)(26), thereby generating rVSV(GP). While there are no doses at which wtVSV can be safely introduced into rodent brains, we found that rVSV(GP) caused no significant neurotoxicity even at doses of 10 8 plaque-forming units (PFU).…”
Section: Introductionmentioning
confidence: 99%
“…A number of VSV mutants have been described (7,11,15,32,33). Attenuation of the VSV phenotype here was done by using either a virus with the cytoplasmic portion of the G protein truncated from 29 amino acids to a single amino acid (VSV-CT1) or by combining an M51 deletion with a partially trun- (2,23,33).…”
Section: Discussionmentioning
confidence: 99%
“…1C). For control vaccine, an attenuated rVSV-N4CT1 HIVgag1 design (20) expressing HIV-1 gag in the first position of the genome was used in animal studies (Fig. 1D).…”
Section: Methodsmentioning
confidence: 99%
“…Attenuation was achieved by combining VSV N gene translocation (N4) with truncation of the VSV G protein cytoplasmic tail domain (CT1) (20). These modifications reduced the intracellular abundance of the major structural N protein (21) and diminished the interaction between the VSV G protein CT domain and the viral nucleocapsid core during particle maturation (22).…”
mentioning
confidence: 99%